Multicore technology : architecture, reconfiguration, and modeling - Samgwine, Stephen J.; Qadri, Muhammad Yasir (Embedded multi-core systems., 2014)
"The saturation of design complexity and clock frequencies for single-core processors has resulted in the emergence of multicore architectures as an alternative design paradigm. Nowadays, multicore/multithreaded computing systems are not only a de-facto standard for high-end applications, they are also gaining popularity in the field of embedded computing. The start of the multicore era has altered the concepts relating to almost all of the areas of computer architecture design, including core design, memory management, thread scheduling, application support, inter-processor communication, debugging, and power management. This book gives readers a holistic overview of the field and guides them to further avenues of research by covering the state of the art in this area. It includes contributions from industry as well as academia"--